2012
DOI: 10.1152/jn.00472.2012
|View full text |Cite
|
Sign up to set email alerts
|

Selection of events in time enhances activity throughout early visual cortex

Abstract: Swallow KM, Makovski T, Jiang YV. Selection of events in time enhances activity throughout early visual cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 85 publications
11
82
0
Order By: Relevance
“…Several studies reported modulations of population activity in human and monkey early visual cortex, which were largely decoupled from cortical stimulus representations but linked to behaviorally relevant events (Cardoso et al 2012;Choe et al 2014;de-Wit et al 2012;Donner et al 2008Donner et al , 2013Jack et al 2006;Hsieh and Tse 2009;Sirotin and Das 2009;Swallow et al 2012;Wilke et al 2006). Specifically, several human fMRI studies reported retinotopically widespread modulations in V1 during perceptual reports in MIB Hsieh and Tse 2009), bistable motion binding (de-Wit et al 2012), and visual discrimination tasks (Choe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported modulations of population activity in human and monkey early visual cortex, which were largely decoupled from cortical stimulus representations but linked to behaviorally relevant events (Cardoso et al 2012;Choe et al 2014;de-Wit et al 2012;Donner et al 2008Donner et al , 2013Jack et al 2006;Hsieh and Tse 2009;Sirotin and Das 2009;Swallow et al 2012;Wilke et al 2006). Specifically, several human fMRI studies reported retinotopically widespread modulations in V1 during perceptual reports in MIB Hsieh and Tse 2009), bistable motion binding (de-Wit et al 2012), and visual discrimination tasks (Choe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hunt and Elliot (1980), in the context of mixed study lists, the visual irregularity of LF-OD words would induce participants to perform a more detailed analysis of their orthographic properties, which in turn offsets any additional processing advantage induced by the ABE. Interestingly, Kirchhoff, Schapiro, & Buckner (2005) reported that the recognition of orthographically distinctive words activated occipital and parietal regions more than did orthographically common words, and Swallow, Makovski and Jiang (2012) found that the detection of auditory targets enhanced activity in the primary visual cortex. This partial overlap in the neural underpinnings of the ABE and the ODE may potentially account for the observed redundancy in their memory consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of other studies using visual/auditory oddball tasks, a cluster of regions were more active after the presentation of target than distractor stimuli, including: the middle and superior frontal gyri of the left hemisphere, the anterior and posterior regions of the right cingulate cortex, the basal ganglia, the thalamus and the insula bilaterally, and the brainstem in the vicinity of the locus coeruleus (LC). Importantly, Swallow, Makovski, and Jiang (2012) found that the presentation of auditory targets led to enhanced activity in the primary visual cortex, whereas the presentation of visual tar gets increased activity in the primary auditory cortex. These find ings suggest that the detection of goal-relevant targets produces cross-modal facilitations in the perceptual processing of back ground stimuli temporally co-occurring with them (Swallow & Jiang, 2013).…”
Section: Cognitive and Neural Mechanisms Of The Abementioning
confidence: 99%
“…Regarding the neural underpinnings of the ABE, an fMRI study showed that the detection of targets induces broad, temporally locked enhancements in cortical regions that are not directly in volved in their processing (Swallow, Makovski, & Jiang, 2012). Participants in these experiments encoded faces, scenes or scram bled images and simultaneously pressed a button whenever a tone of a predefined pitch was presented over headphones (or a square of a given color appeared on the screen).…”
Section: Cognitive and Neural Mechanisms Of The Abementioning
confidence: 99%